Carbonyl-rich 3D zinc powder anode, symmetric battery and preparation method of symmetric battery

By constructing a carbonyl-rich 3D structure on the surface of zinc powder, the problems of low zinc utilization and serious side reactions of traditional zinc foil negative electrode materials are solved, and the zinc ion flux is uniformized and the side reactions are suppressed, which significantly improves the cyclic stability of zinc powder anode and the performance under high current density.

CN119650586APending Publication Date: 2025-03-18NINGBO INST OF NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411769323.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Traditional zinc foil negative electrode materials have problems such as low zinc utilization, serious side reactions and poor cycle stability, especially under high current density conditions.

Method used

By constructing a carbonyl-rich 3D structure on the surface of zinc powder, using a nonionic surfactant and a carbonyl organic acid layer, the zinc ion flux and interface stability are adjusted, side reactions are inhibited and uniform deposition is promoted.

Benefits of technology

The uniformization of zinc ion flux and inhibition of side reactions are achieved, which significantly improves the cyclic stability of zinc powder anode and the performance under high current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650586A_ABST
    Figure CN119650586A_ABST
Patent Text Reader

Abstract

The invention provides a carbonyl-rich 3D zinc powder anode, a symmetric battery and a preparation method of the symmetric battery, and belongs to the field of water system energy storage batteries, and the preparation method of the carbonyl-rich 3D zinc powder anode specifically comprises the following steps: preparing a nonionic surfactant aqueous solution; zinc powder is put into the nonionic surfactant aqueous solution, and 3D printing zinc powder ink is obtained; converting the 3D printing zinc powder ink into a semi-solid state, and transferring the 3D printing zinc powder ink into a needle cylinder; a preset structure is printed on the base plate through an extrusion type 3D printer, and the 3D printing zinc powder support is obtained after printing is completed; treating the 3D printing zinc powder bracket to obtain a semi-finished product; and placing the semi-finished product in a carbonyl-containing organic acid aqueous solution for reaction to obtain the product. According to the invention, the capability of damaging a Zn < 2 + > solvation structure by OAZ molecules at an interface and the Zn < 2 + > ion flux are adjusted and optimized by adjusting the carbonyl content on the surface of 3D Zn, side reactions can be obviously reduced, Zn < 2 + > is induced to be uniformly deposited, and good cycle stability is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of aqueous energy storage batteries, and in particular relates to a carbonyl-rich 3D zinc powder anode, a symmetrical battery and a preparation method thereof. Background Art

[0002] Conventional lithium-ion batteries (LIBs) have become the main rechargeable energy supply in many fields, from consumer devices and electric vehicles to power grids, due to their excellent energy density and high cycle stability. However, with the large-scale commercial application of lithium-ion batteries, the price of lithium resources has continued to rise, and its safety issues have also been frequently reported, so it is necessary to find alternative electrochemical energy storage. Rechargeable aqueous batteries, especially zinc-ion batteries (AZIBs), are considered to be promising battery systems for grid-level energy storage and flexible wearable devices due to their high safety, easy assembly, low cost, abundant zinc resources, and environmental friendliness.

[0003] Commercial zinc foil (thick electrode, usually >80μm) has been widely used as anode material in recent studies due to its low cost and ease of use. However, thick zinc anodes usually have a large negative electrode / positive electrode (N / P) mass ratio (>50%), insufficient utilization, and low depth of discharge (DOD<3%), which leads to insufficient utilization of zinc. In contrast, zinc powder (ZnP), as a common negative electrode material, has outstanding advantages in cost, large-scale processing, versatility, and adjustability in actual industrial applications. In particular, granular zinc powder is adjustable in particle size distribution and dosage, and can balance the N / P ratio to achieve high utilization of zinc anode. However, compared to zinc foil Zn 2+ Preferential deposition on the convex surface of ZnP results in dendrites similar to those seen in zinc foil. More seriously, the high contact area of ​​ZnP in aqueous electrolyte exacerbates the inherent instability of metallic zinc, leading to more severe corrosion and hydrogen evolution. This will increase the internal pressure of the battery and damage the sealing, ultimately leading to battery failure. In addition, repeated uneven Zn 2+ The deposition / stripping process causes the connection between ZnP particles and the conductive skeleton to loosen, resulting in the formation of "dead zinc" during the cycle.

[0004] In order to solve the above problems, an effective method is to reduce the side reactions while inducing Zn 2+ One method is to construct a zinc-philic interface layer on the surface of zinc powder, which can reduce the contact between zinc powder and active water molecules, reduce side reactions, and provide a stable interface for electrochemical reactions. For example, methods such as covering the surface of zinc powder with MXene, PEG coating, graphene, and nitrogen-doped carbon. Another feasible method is to increase the ion flux by designing a reasonable structure to uniformly distribute the electric field. Specifically, the reasonable design of the structure makes the electric field distribution of the electrode uniform, thereby promoting Zn 2+The deposition is more uniform. However, the trade-off between 3D structure design and side reaction suppression is also difficult to achieve, because the increase in the contact area between the electrode and the electrolyte will aggravate the side reactions of the electrode. Considering the above issues, designing additive-free 3D zinc powder-based electrodes with appropriate surface coatings will be a promising strategy to well suppress the growth of zinc dendrites and achieve high current density / capacity (≥5 mA(h)cm -2 ) conditions to achieve durable performance. Therefore, the development of a low-cost electrolyte with high zinc adsorption is of great practical significance. Summary of the invention

[0005] The purpose of the present invention is to provide a carbonyl-rich 3D zinc powder anode, a symmetrical battery and a preparation method thereof. The prepared carbonyl-rich 3D zinc powder anode not only provides a high zinc ion flux, but also the prepared zinc ion symmetrical battery has good cycle stability.

[0006] The present invention provides a method for preparing a carbonyl-rich 3D zinc powder anode, and the preparation method specifically comprises the following steps:

[0007] S1, dissolving nonionic surfactant powder in deionized water, and obtaining a nonionic surfactant aqueous solution after stirring;

[0008] S2, adding zinc powder into the non-ionic surfactant aqueous solution obtained in step S1, and obtaining 3D printing zinc powder ink after stirring;

[0009] S3, transforming the 3D printing zinc powder ink obtained in step S2 into a semi-solid state after static treatment, and transferring the semi-solid state into a 3D printing syringe;

[0010] S4, using an extrusion 3D printer to print a preset structure on the substrate, and after printing, drying is performed to obtain a 3D printed zinc powder bracket;

[0011] S5, subjecting the 3D printed zinc powder bracket obtained in step S4 to degreasing, cooling and sintering treatments in sequence to obtain a semi-finished product;

[0012] S6, placing the semi-finished product obtained in step S5 in an aqueous solution of an organic acid containing a carbonyl group to react, and after the reaction is completed, washing and drying to obtain a carbonyl-rich 3D zinc powder anode.

[0013] The present invention discloses a method for preparing a carbonyl-rich 3D zinc powder anode, and the carbonyl content on the surface of 3D Zn is adjusted to adjust and optimize the OAZ molecules at the interface to destroy Zn. 2+ Solvation structure ability and Zn 2+ Ion flux can significantly reduce side reactions and induce Zn 2+ Uniform deposition and good cycle stability are achieved.

[0014] In some embodiments, in step S1, the nonionic surfactant is Pluronic F127, and the mass ratio of Pluronic F127 powder to deionized water is 1:2.5-3.5, and the prepared nonionic surfactant aqueous solution is stored at 3°C.

[0015] Compared with the prior art, the present invention adopts the above raw materials to prepare a non-ionic surfactant aqueous solution, wherein Pluronic F127 is a polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer, which has good surface activity and dispersibility. By controlling its concentration, zinc powder particles can be effectively dispersed to prevent them from agglomerating in the solution, thereby ensuring good fluidity of the ink during 3D printing and consistency of the structure after printing.

[0016] In some embodiments, in step S2, the volume of the non-ionic surfactant aqueous solution is 4-6 ml, and the mass of the zinc powder is 18-24 g.

[0017] Compared with the prior art, the present invention adopts the above-mentioned mass and volume configuration of 3D printing zinc powder ink. This ratio range is intended to ensure that the final ink has a viscosity suitable for the 3D printing process. Too thin ink may result in an unstable printed structure, while too thick ink may affect the fluidity and uniformity during the printing process. By adjusting the ratio of solid content (zinc powder) to liquid medium, the rheological properties of the ink can be optimized.

[0018] In some embodiments, in step S3, the parameters of the static treatment are as follows: temperature is 25° C., and time is 5 min.

[0019] Compared with the prior art, the present invention is subjected to a static treatment. The short static treatment helps to make the zinc powder particles more evenly distributed in the solution and reduce the local aggregation phenomenon that may be generated during the stirring process, which can improve the material consistency in the subsequent 3D printing process.

[0020] In some embodiments, in step S3, the parameters of the drying process are as follows: temperature is 25° C., and time is 8 hours.

[0021] Compared with the prior art, the advantages of the above-mentioned drying treatment parameters adopted in the present invention are: the lower drying temperature (25°C) can slow down the evaporation rate of water, thereby reducing the internal stress accumulation caused by rapid drying and reducing the risk of cracks or deformation; and the 8-hour drying process allows water to escape from the material more evenly, ensuring that the entire electrode structure can be fully dried inside and outside, which is beneficial to improving the mechanical strength and consistency of the final product.

[0022] In some embodiments, in step S3, the model of the 3D printer is Fisnar DSP501N, the ink pressure is 50-60 psi, and the printing speed is 5 mm s -1 .

[0023] Compared with the prior art, the advantages of the present invention using the above 3D printing parameters are: Fisnar DSP501N is a precision dispensing system suitable for high-precision material distribution. It can provide stable extrusion control, which is very important for forming accurate and consistent 3D structures; and the pressure range of 50-60psi helps to ensure that the ink will not flow smoothly due to too low pressure during the extrusion process, nor will it cause excessive extrusion or material waste due to too high pressure. This pressure range can ensure that the ink is extruded at an appropriate rate and uniformity.

[0024] In some embodiments, in step S5, the specific steps of the degreasing treatment are as follows: heating to 400° C. at a rate of 2-5° C. / min and maintaining for 8-10 hours;

[0025] The specific steps of the cooling treatment are as follows: cooling to room temperature at a rate of 2-5°C / min;

[0026] The specific steps of the sintering treatment are as follows: heating to 600° C. at a rate of 2-5° C. / min and maintaining for 1-2 hours.

[0027] Compared with the prior art, the present invention adopts the above-mentioned parameters of degreasing and sintering treatment, which have the following effects: 2-5°C / min helps to make the temperature distribution inside the material more uniform, reduces the thermal stress and possible cracks caused by rapid heating, and segmented heating allows different physical and chemical reactions of the material at different temperatures, thereby optimizing the performance of the final product; and high temperature (600°C) and short-time heat preservation (1-2 hours) can further enhance the bonding strength between particles and improve the mechanical stability and conductivity of the electrode.

[0028] In some embodiments, in step S5, the carbonyl-containing organic acid is selected from one of methacrylic acid, acrylic acid, butyric acid and 2,2-dimethylpropionic acid, and the concentration is 0.03-0.1 mol / L, and the reaction time is 30 min;

[0029] Compared with the prior art, the present invention proposes a 3D zinc powder anode treated with a carbonyl-rich organic acid. This carbonyl-rich structure has a high polarity and can destroy the solvation structure of water molecules at the interface between the electrode and the electrolyte, and the carbonyl group therein can form Zn 2+ channel, further inducing Zn 2+By adjusting the concentration of the organic acid aqueous solution for treating 3D zinc, the carbonyl content on the surface of zinc powder and the ability to destroy the solvation structure of water molecules can be effectively adjusted, thereby inhibiting the side reactions of the zinc powder anode during the cycle and promoting the Zn 2+ The rapid deposition of zinc powder anode slows down the serious side reactions caused by the large specific surface area of ​​zinc powder anode and increases the actual cycle life of zinc powder anode under high current density conditions.

[0030] The second object of the present invention is to provide a carbonyl-rich 3D zinc powder anode, which is prepared by the above preparation method.

[0031] Compared with the prior art, the present invention prepares a carbonyl-containing multifunctional zinc organic acid layer (OAZ) on the surface of a three-dimensional (3D) zinc powder anode by in-situ modification. The OAZ layer with high electronegativity and high nucleophilic carbonyl helps Zn 2+ The desolvation process and ion flux are homogenized. In addition, the hydrophobic carbon chains in OAZ can reduce the direct contact between Zn powder and free water, significantly improving the ability to resist side reactions. Finally, through the synergistic effect of OAZ and 3D Zn structure, the prepared electrode can achieve a high conductivity at 5 mA cm -2 / 5mAhcm -2 Stable cycle for 650h under the conditions of

[0032] The third object of the present invention is to provide a symmetrical battery, wherein the symmetrical battery comprises a carbonyl-rich 3D zinc powder anode.

[0033] A fourth object of the present invention is to provide a method for preparing a symmetrical battery, the method comprising the following steps:

[0034] S1. Trimming the electrode: After trimming and polishing the edge of the carbonyl-rich 3D zinc powder anode, immerse it in anhydrous ethanol and perform ultrasonic treatment for 5-10 minutes to remove surface impurities, then take it out of the anhydrous ethanol and blow dry it at room temperature for later use;

[0035] S2. Take the carbonyl-rich 3D zinc powder anode, glass fiber separator and 2M ZnSO4 electrolyte obtained in the two steps S1 and assemble them to obtain a symmetrical battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The scanning electron microscope images of the carbonyl-rich 3D zinc powder anode prepared in Example 1 and Comparative Example 1 after being immersed in 2M ZnSO4 electrolyte for seven days;

[0037] Figure 2 The figure is a relationship diagram between the coulombic efficiency and the number of cycles of the symmetrical batteries prepared in Example 5 and Comparative Example 3;

[0038] Figure 3The symmetrical cells prepared in Example 6 and Comparative Example 3 were -2 The current density and 2 mAh cm -2 Cycle curve diagram under capacity conditions;

[0039] Figure 4 The symmetrical cells prepared in Example 5 and Comparative Example 3 were -2 The current density and 5 mAh cm -2 Cycle curve diagram under capacity. DETAILED DESCRIPTION

[0040] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.

[0041] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0042] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.

[0043] The technical effects of the present invention are described below in conjunction with specific embodiments.

[0044] Example 1

[0045] This embodiment provides a carbonyl-rich 3D zinc powder anode, which is prepared by the following preparation method:

[0046] S1. Dissolve 1.67 g of Pluronic F127 powder in 5 mL of deionized water, stir to obtain a Pluronic F127 aqueous solution, and store in a refrigerator at 3°C ​​overnight;

[0047] S2. Place 20 g of commercial zinc powder in the Pluronic F127 aqueous solution obtained in step S1, and obtain 3D printing zinc powder ink after stirring.

[0048] S3, placing the 3D printing zinc powder ink prepared in S2 at 25°C for 5 minutes, and transferring it to a 3D printing syringe after the temperature rises and it turns into a semi-solid state;

[0049] S4: Use an extrusion 3D printer (Fisnar DSP501N) to print the preset structure on the substrate. The ink pressure is controlled at 50-60psi and the printing speed is maintained at 5mm s -1 After printing is completed, it is dried at 25°C for 8 hours to obtain a 3D printed zinc powder bracket.

[0050] S5, heating the obtained 3D zinc powder scaffold to 400°C at a rate of 5°C / min in a muffle furnace, maintaining it for 8 hours, and then maintaining it at 600°C for 1 hour at the same rate to obtain 3D Zn;

[0051] S6. Place 3D Zn in 100 mL of 0.03 mol / L methacrylic acid aqueous solution and react for 30 min. Wash with deionized water and dry to obtain a carbonyl-rich 3D zinc powder anode, named ZMA@3D Zn.

[0052] Example 2

[0053] This embodiment provides a carbonyl-rich 3D zinc powder anode, which is different from Embodiment 1 only in that in step S6 of this embodiment, the concentration of the methacrylic acid aqueous solution is 0.05 mol / L, and the rest is the same as Embodiment 1 and will not be repeated here.

[0054] Example 3

[0055] The present embodiment provides a carbonyl-rich 3D zinc powder anode, which is different from the embodiment 1 only in that the specific steps of step S5 of the present embodiment are: heating the obtained 3D zinc powder bracket to 400°C at a rate of 5°C / min in a muffle furnace, maintaining for 8 hours, and then maintaining at 600°C for 2 hours at the same rate to obtain 3D Zn. The rest is the same as the embodiment 1 and will not be repeated here.

[0056] Example 4

[0057] This embodiment provides a carbonyl-rich 3D zinc powder anode, which is different from Embodiment 3 only in that in step S6 of this embodiment, the concentration of the methacrylic acid aqueous solution is 0.05 mol / L, and the rest is the same as Embodiment 3 and will not be repeated here.

[0058] Example 5

[0059] This embodiment provides a symmetrical battery, which is prepared by the following preparation method:

[0060] S1. Trimming ZMA@3D Zn: trimming the edges of ZMA@3D Zn in the two embodiments 1 completely without obvious protrusions;

[0061] S2. Assemble the trimmed ZMA@3D Zn electrode, glass fiber separator and 100 μL 2M ZnSO4 electrolyte in step S1 to obtain a symmetrical battery.

[0062] Example 6

[0063] This embodiment provides a symmetrical battery, which is prepared by the following preparation method:

[0064] S1. Trimming ZMA@3D Zn: trimming the edges of ZMA@3D Zn in the two embodiments 2 completely without obvious protrusions;

[0065] S2. Assemble the trimmed ZMA@3D Zn electrode, glass fiber separator and 100 μL 2M ZnSO4 electrolyte in step S1 to obtain a symmetrical battery.

[0066] Comparative Example 1

[0067] This comparative example provides a carbonyl-rich 3D zinc powder anode. The only difference from Example 1 is that this comparative example does not include step S6. The rest is the same as Example 1. The obtained sample is named 3D Zn and will not be described again here.

[0068] Comparative Example 2

[0069] This comparative example provides a carbonyl-rich 3D zinc powder anode, which is different from Example 3 only in that this comparative example does not include step S6, and the rest is the same as Example 3. The obtained sample is named 3D Zn, which will not be described again here.

[0070] Comparative Example 3

[0071] This comparative example provides a symmetrical battery, which is prepared by the following preparation method:

[0072] S1, trimming ZMA@3D Zn: the edges of ZMA@3D Zn in the two comparative examples 1 were trimmed completely without obvious protrusions;

[0073] S2. Assemble the trimmed ZMA@3D Zn electrode, glass fiber separator and 100 μL 2M ZnSO4 electrolyte in step S1 to obtain a symmetrical battery.

[0074] Test part:

[0075] 1. The 3D zinc powder anodes prepared in Example 1 and Comparative Example 1 were immersed in 2M ZnSO4 zinc ion battery electrolyte, and the zinc deposition behavior was preliminarily observed and verified by in-situ optical microscopy. -2 At current densities of 200 Å, 3D Zn exhibited severe structural damage and corrosion over time. In contrast, ZMA@3D Zn was deposited uniformly without obvious corrosion. Scanning electron microscopy (SEM) images also showed that the ZMA@3D Zn surface was densely and uniformly deposited with zinc, while the 3D Zn surface was rich in dendrites ( Figure 1 ).

[0076] 2. The symmetrical batteries prepared in Example 5 and Comparative Example 3 were tested for performance. The test results are as follows: Figure 2 As shown, from Figure 2 It can be seen that the relationship between coulombic efficiency and cycle number ZMA@3D Zn / Cu half-cell is more stable than 3D Zn / Cu half-cell in Coulombic efficiency (CE), which is maintained above 99%, proving that it has good deposition / stripping reversibility.

[0077] 3. The symmetrical cells prepared in Example 6 and Comparative Example 3 were heated at 4 mA cm -2 The current density and 2 mAh cm -2 Under the capacity of , the performance test is carried out, and the test results are as follows Figure 3 As shown, from Figure 3 It can be seen that ZMA@3D Zn at 4 mA cm -2 / 2mAh cm -2 The 3D Zn layer could be stably cycled for 500 hours under the conditions of 40 hours, while the 3D Zn layer short-circuited after only 40 hours of cycling.

[0078] 4. The symmetrical cells prepared in Example 5 and Comparative Example 3 were heated at 5 mA cm -2 The current density and 5 mAh cm -2 Under the capacity of , the performance test is carried out, and the test results are as follows Figure 4 As shown, from Figure 4 It can be seen that ZMA@3D Zn at 5 mA cm -2 / 5mAh cm -2 The 3D Zn nanostructured samples can be stably cycled for 650 h under the same conditions, while the 3D Zn nanostructured samples quickly show polarization.

[0079] Although the disclosure is disclosed as above, the protection scope of the disclosure is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing a carbonyl-rich 3D zinc powder anode, characterized in that: The preparation method specifically comprises the following steps: S1, dissolving nonionic surfactant powder in deionized water, and obtaining a nonionic surfactant aqueous solution after stirring; S2, adding zinc powder into the non-ionic surfactant aqueous solution obtained in step S1, and obtaining 3D printing zinc powder ink after stirring; S3, transforming the 3D printing zinc powder ink obtained in step S2 into a semi-solid state after static treatment, and transferring the semi-solid state into a 3D printing syringe; S4, using an extrusion 3D printer to print a preset structure on the substrate, and after printing, drying is performed to obtain a 3D printed zinc powder bracket; S5, subjecting the 3D printed zinc powder bracket obtained in step S4 to degreasing, cooling and sintering treatments in sequence to obtain a semi-finished product; S6, placing the semi-finished product obtained in step S5 in an aqueous solution of an organic acid containing a carbonyl group to react, and after the reaction is completed, washing and drying to obtain a carbonyl-rich 3D zinc powder anode.

2. The preparation method according to claim 1, characterized in that In the step S1, the nonionic surfactant is Pluronic F127, and the mass ratio of Pluronic F127 powder to deionized water is 1:2.5-3.

5. The prepared nonionic surfactant aqueous solution is stored at 3°C.

3. The preparation method according to claim 1, characterized in that: In step S2, the volume of the non-ionic surfactant aqueous solution is 4-6 ml, and the mass of the zinc powder is 18-24 g.

4. The preparation method according to claim 1, characterized in that: In step S3, the parameters of the static treatment are as follows: temperature is 25° C., time is 5 min; And / or, in step S3, the parameters of the drying process are as follows: temperature is 25° C., and time is 8 hours.

5. The preparation method according to claim 1, characterized in that: In step S3, the model of the 3D printer is Fisnar DSP501N, the ink pressure is 50-60 psi, and the printing speed is 5 mm s -1 .

6. The preparation method according to claim 1, characterized in that: In step S5, the specific steps of the degreasing treatment are as follows: heating to 400°C at a rate of 2-5°C / min and maintaining for 8-10h; The specific steps of the cooling treatment are as follows: cooling to room temperature at a rate of 2-5°C / min; The specific steps of the sintering treatment are as follows: heating to 600° C. at a rate of 2-5° C. / min and maintaining for 1-2 hours.

7. The preparation method according to claim 1, characterized in that: In step S5, the carbonyl-containing organic acid is selected from one of methacrylic acid, acrylic acid, butyric acid and 2,2-dimethylpropionic acid, and has a concentration of 0.03-0.1 mol / L. The reaction time is 30 min.

8. A carbonyl-rich 3D zinc powder anode, characterized in that: The method is prepared by any one of claims 1 to 7.

9. A symmetrical battery, characterized in that: The symmetrical battery comprises the carbonyl-rich 3D zinc powder anode of claim 8.

10. The method for preparing a symmetrical battery according to claim 9, characterized in that: The preparation method specifically comprises the following steps: S1. Trimming the electrode: After trimming and polishing the edge of the carbonyl-rich 3D zinc powder anode, immerse it in anhydrous ethanol and perform ultrasonic treatment for 5-10 minutes to remove surface impurities, then take it out of the anhydrous ethanol and blow dry it at room temperature for later use; S2. Take the carbonyl-rich 3D zinc powder anode, glass fiber separator and 2M ZnSO4 electrolyte obtained in the two steps S1 and assemble them to obtain a symmetrical battery.